Involvement of brain cell phenotypes in stress-vulnerability and resilience - Favoretto, Cristiane Aparecida; Pagliusi, Marco; Morais-Silva, Gessynger [UNESP] (Frontiers, 2023)
Stress-related disorders’ prevalence is epidemically increasing in modern society, leading to a severe impact on individuals’ well-being and a great economic burden on public resources. Based on this, it is critical to understand the mechanisms by which stress induces these disorders. The study of stress made great progress in the past decades, from deeper into the hypothalamic–pituitary–adrenal axis to the understanding of the involvement of a single cell subtype on stress outcomes. In fact, many studies have used state-of-the-art tools such as chemogenetic, optogenetic, genetic manipulation, electrophysiology, pharmacology, and immunohistochemistry to investigate the role of specific cell subtypes in the stress response. In this review, we aim to gather studies addressing the involvement of specific brain cell subtypes in stress-related responses, exploring possible mechanisms associated with stress vulnerability versus resilience in preclinical models. We particularly focus on the involvement of the astrocytes, microglia, medium spiny neurons, parvalbumin neurons, pyramidal neurons, serotonergic neurons, and interneurons of different brain areas in stress-induced outcomes, resilience, and vulnerability to stress. We believe that this review can shed light on how diverse molecular mechanisms, involving specific receptors, neurotrophic factors, epigenetic enzymes, and miRNAs, among others, within these brain cell subtypes, are associated with the expression of a stress-susceptible or resilient phenotype, advancing the understanding/knowledge on the specific machinery implicate in those events.
Keywords: brain cell phenotypes; brain cell populations; resilience; stress outcomes; vulnerability